Sleep Medicine Milestones 2.0: designed for our field - Dredla, Brynn K. (J Clin Sleep Med, 2021)
The Accreditation Council for Graduate Medical Education published the first sleep medicine milestones in 2015. However, these milestones were the same among all internal medicine fellowship programs; they were not specific to the specialty. Based on stakeholder feedback, the Accreditation Council for Graduate Medical Education called for the creation of specialty-specific milestones. Herein, we outline the history of Accreditation Council for Graduate Medical Education reporting milestones; the identification of knowledge, skills, and attitudes that define the practice of sleep medicine; and the creation of the supplemental guide and sleep medicine–specific milestones (Sleep Medicine Milestones 2.0) to assess developmental progression during fellowship training. CITATION: Dredla BK, Edgar L, Samman H, et al. Sleep Medicine Milestones 2.0: designed for our field. J Clin Sleep Med. 2021;17(3):499–503.